An overview of rattan industry status and its economic aspect in setting up rattan-based industry in Malaysia - Razak Wahab,; Nasihah Mokhtar,; Ros Syazmini Mohd Ghani,; Mohamad Saiful Sulaiman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Rattan constitutes the most abundant non-timber forest products that could be used as a substitute for wood in the form of furniture and other products in many communities, especially in Malaysia. This study makes an explorative overview of two main research topics in forest resources management which are determined the status of the rattan industry and their economics aspect in Malaysia. Malaysia is among the top most crucial rattan producers in the world. The country is experiencing a robust development in the rattan industry. This commodity plays a significant role in the Malaysia economic growth. There are a few processes or techniques which are vital in this industry. Malaysia is the second in the rank after Indonesia for the rattan industry. In addition, the viability of rattan furniture manufacturing as a business is determined through cost and profit analyses and the results discussed in this review.